Visible Light‐Induced Photoeletrochemical and Antimicrobial Properties of Hierarchical CuBi2O4 by Facile Hydrothermal Synthesis. Issue 8 (6th June 2016) - Zhu, Lu; Basnet, Pradip; Larson, Steven R.; Jones, Les P.; Howe, Jane Y.; Tripp, Ralph A.; Zhao, Yiping
Abstract: Narrow bandgap semiconductor CuBi2 O4 microstructures such as three dimensional hierarchical microspheres, micro‐flowers, one dimensional microrods and nanorods were fabricated through a facile hydrothermal synthesis approach by systematically changing the synthesis conditions. Their optical properties and photocatalytical performances under visible light illumination were characterized. The hierarchical micro‐flower shaped CuBi2 O4 sample showed a high photodecay rate of 0.114 ± 0.002 h −1 with 1 mg/ml CuBi2 O4 concentration for methylene blue (30 μM). Under the illumination of an AM 1.5G solar simulator, a 0.02 mA/cm 2 stable cathodic photocurrent density was observed at a low negative bias voltage (‐0.25 V vs (Ag/AgCl)). The micro‐flower shaped CuBi2 O4 sample also showed a high antibacterial effect against Escherichia coli, with ∼ 93 % bacteria reduction after 6 h illumination by a commercial white LED light (10 mW/cm 2 ). These results indicate that CuBi2 O4 can be a promising candidate for visible light driven energy conversion and antimicrobial applications. Abstract : Different CuBi2 O4 micro‐/nanostructures were synthesized by facial hydrothermal method and tested for photocatalytic performances. The hierarchical micro‐flower shaped CuBi2 O4 sample showed a high antibacterial effect against Escherichia coli, with ∼ 93 % bacteria reduction after 6 h illumination by a commercial white LED light.